Developing module of digital communication for professional contexts - Permatasari, Alfelia Nugky; Soelistiyowati, Endang; Vardhani, Nabilla Kusuma; Nugroho, Vincentius Tangguh Atyanto (INVOTEC, 2023)
This study aims to develop digital communication module that can be used by the general public for professional communication contexts. The module has been developed using the Define, Design, Development, Dissemination (4D) model: Define includes determining a digital communication platform along with the goals and etiquette needed; Design includes making a blueprint for the module; Development includes the development of the module as a whole by involving expert judgment; then Dissemination includes dissemination/publication of the module. From the Define and Design stages, the initial design of the module is obtained. Expert assessment at the Development stage shows that the module design is useful for audiences and is appropriate for dissemination with minor improvements for further dissemination in a form of a book at the Dissemination stage.